Knee laxity of Malaysian adults: gender differentials, and association with age and anthropometric measures - Zyroul, R.; Hossain, M.G.; Azura, M.; Abbas, A.A.; Kamarul, Tunku (0968-0160, 2013)
Background: Knee laxity measurements have been shown to be associated with some medical conditions such as chronic joint pain and collagen tissue diseases. The aim of this study was to determine the effects of demographic factors and anthropometric measures on knee laxity. Materials and methods: Data were collected from 521 visitors, staffs and students from the University Malaya Medical Centre and University of Malaya between December 2009 and May 2010. Knee laxity was measured using a KT-1000 arthrometer. Multiple regression analysis was used to find the association of knee laxity with age and anthropometric measures. Results: Using ANOVA, knee laxity did not show significant differences among ethnic groups for both genders. The average knee laxity in men was 3.47mm (right) and 3.49mm (left); while in women were 3.90mm (right) and 3.67mm (left). Knee laxity in women was significantly higher (right knee p<0.01 and left knee p<0.05) than men. Right knee laxity of men was negatively associated with height (p<0.05) and BMI (p<0.05); also a negative association was observed between left knee laxity and BMI (p<0.05). Overweight and obese men had less knee laxity than normal weight and underweight individuals. Elderly men and women (age 55 and above) had lower knee laxity (p<0.01) than young adults (ages 21â39). Conclusion: These results suggest that age and body size are important factors in predicting knee laxity.